Relación entre intolerancia a la incertidumbre y ansiedad en adultos jóvenes - Reyes Ruiz, Ivana Lizeth (2024)
Anxiety and intolerance of uncertainty are psychological phenomena that have been increasing in recent years. The increase in these mental health problems is related to the COVID-19 pandemic and the measures that were implemented to stop its spread. In this way, it is established that the prevalence of these phenomena can be harmful; especially in the young adult population. The objective of this study is to identify the relationship between intolerance of uncertainty and anxiety in young adults. In order to fulfill this purpose, a review was carried out through the Scopus, Pubmed and APA Psycnet databases. 10 articles were selected, between the years 2017 and 2024, which met the corresponding inclusion and exclusion criteria and had a correlational design. The main previous results are that intolerance of uncertainty has a significant and positive relationship with anxiety